The first aerial survey to estimate abundance of humpback whales (Megaptera novaeangliae) in the breeding ground off Brazil (Breeding Stock A) - Andriolo , A.; Martins , C. C. A.; Engel , M. H.; Pizzorno , J. L.; Mas-Rosa , S.; Freitas , A. C.; Morete , M. E.; Kinas , P. G. (J. Cetacean Res. Manage., 2023)
In the Southern Hemisphere, humpback whales (Megaptera novaeangliae) were heavily exploited from both coastal stations and in pelagic waters in all major ocean basins. About 200,000 whales were taken after 1900, causing declines of populations to small percentages of their pre-exploitation levels. The study presented here aimed to investigate humpback whale abundance in the Brazilian coastal breeding ground, in order to provide information to support further analysis of the population recovery. Between 25 August and 2 September 2001, a fixed wing, flat window, aircraft was used to survey transect lines along the northern limit of Bahia State (12°10’S), to the southern limit of Espírito Santo State (20°42’S). All on-effort sightings were recorded and abundance was estimated according to standard distance sampling methodology (Burnham et al., 1980; Buckland et al., 1993). Group sizes of humpback whales ranged between 1-5 and the mean group size was 1.52 (±0.06). The model that best fitted the perpendicular distance data, based on the minimum Akaike Information Criterion, was the hazard rate model. The population size estimated using uncorrected data was 1,493 (CV=0.21) whales. Surface time was used to correct the estimates for gˆ(0), resulting in a correction factor of 0.67 (±0.15). The corrected analysis for each block and combined result, increased the population size estimate to 2,229 (CV=0.31) individuals. The data from this study could be used to identify new areas appropriate for whalewatching, to monitor the status and dynamics of the humpback whale population off the Brazilian coast and to provide information for the establishment of new protected areas.